Generation Z, values, and media: from influencers to BeReal, between visibility and authenticity - Tirocchi, Simona (Frontiers in Sociology, 2024)
This study examines the connection between values perceived as important by Generation Z and the values conveyed by the media contents chosen and consumed by young individuals. The article’s main objective is to identify the values that a sample of Italian university students, aged between 20 and 23, consider most significant. It explores their perceptions and expectations regarding contemporary society and the ethical trends therein. Furthermore, it investigates their preferred media and the values they believe these media platforms convey, trying to investigate the relationship between values and favorite media. Media and digital platforms, indeed, play an increasingly vital role in shaping and disseminating values. YouTubers, influencers, or, in a broader context, content on social media platforms (such as Instagram, TikTok, as well as entertainment platforms like Netflix) demonstrate how the new mediators of communication and the forms of media content favored by young individuals are, more evidently than ever, intertwined with the sharing of values, norms, and social expectations, much like family and school once were. One example that emerged from the research concerned the success of the “Bereal” platform, linked on the one hand to the desire to make public and share one’s self-image, and on the other hand to the need to show oneself as “authentic.” Through the conduct of five focus groups in December 2022 involving 60 university students from the University of Turin, this research reveals a substantial continuity in the values considered most important by young individuals (compared to previous national surveys). The article also demonstrates how the values conveyed by the media favored by young people do not always correspond to traditional ones and express needs that, at times, the new digital platforms and their protagonists manage to intercept.